Introducing Media Education in the Early Childhood Curriculum in Tanzania - Mtahabwa, Lyabwene (Papers in Education and Development, 2018)
The mass media exert tremendous influence globally and on individual states, affecting all members of society of different ages in all walks of life. The unprecedented increase in communication technology has accelerated this trend. In urban and rural areas at home, school, and worship places or on the streets; the cultural values, norms, beliefs and attitudes are continually being altered by media messages. These messages are delivered in various forms, aimed at achieving specific goals for specific groups of people. Children ' s high receptivity and absorption of information indiscriminately renders them vulnerable to developing unwanted socio-cultural behaviours. This article builds a case for an urgent need to introduce and implement media education in early childhood programmes in Tanzania as a way of curbing adverse media influences on young children. Key words: Media education, early childhood programmes, Tanzania.